Publisher Correction: Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. (December 2018) - Evangelou, Evangelos; Warren, Helen; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia; Karaman, Ibrahim; Ng, Fu; Evangelou, Marina; et al.
In the version of this article originally published, the name of author Martin H. de Borst was coded incorrectly in the XML. The error has now been corrected in the HTML version of the paper.